Combination of Autoclave Treatment and NDIR Process Analytics for Quantification of Aluminum Carbide in Powdery Samples - Niedermayer, Stefan Rudolf; Ellersdorfer, Markus (Analytica, 2022)
Aluminum Carbide (Al4C3) is a main source of corrosion problems in metal matrix composites as well as refractory products. Hydrolysis to methane happening at room temperature leads to various structural problems. As methods to quantify Al4C3 are scarce, this paper proposes a method to measure Al4C3 containing analyte powders in mg areas by combining a robust autoclave system with non-dispersive infrared (NDIR) process analytics. The method uses only water as reagent, making it easy and safe to handle. The used materials were characterized by thermogravimetric analysis coupled with fourier-transformation infrared detection (TGA-IR), LECO-C analysis, and X-ray diffraction (XRD) before and after autoclave treatment. 90–90.8% recovery of 100 mg Al4C3 with small standard deviations (<1% at n = 3) in 240, 205, and 165 min at 60, 70, and 80 °C, respectively, were achieved. XRD analysis showed the total conversion of Al4C3 to Bayerite (Al(OH)3) and Boehmite (AlO(OH)) at 70 °C. Comparison with shrinking core models showed that the reaction is neither purely reaction nor purely ash diffusion controlled. The findings indicate possibilities for further acceleration of reaction speeds by increasing temperature. The 200 mL reactor volume of the autoclave enables the analysis of bigger sample sizes at temperatures above 100 °C by separating reaction and analysis procedure. This provides an extension to gas chromatographic methods for industrial quality control of bulk materials in rougher environments.